Konteks Late Antiquity dan Analisis Struktur Mikro sebagai Counter atas Skeptisisme Orisinalitas Teks Al-Qur’an: - Adrika Fitrotul Aini; Asep Nahrul Musadad (Lajnah Pentashihan Mushaf Al-Qur'an, 2017)
This article tries to discuss the reading of Angelika Neuwirth to the holy Qur'an by using critical historical approach through the focus of Qur'anic study before canonical phase. The reading by involving